2010
DOI: 10.1029/2009ja014273
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh‐Taylor type instability in auroral patches

Abstract: [1] Based on observations by a high-resolution narrow field-of-view CCD camera, we found small-scale (5-25 km) finger-like structures at the western boundary of auroral patches in images obtained at Gillam (geomagnetic latitude: 65.5°N), Canada, in January 2008. Since shear motion was not observed along the boundary of the patches, we suggest that these structures are formed by macroscopic Rayleigh-Taylor type plasma instability arising in the magnetospheric equatorial plane from the force balancing of the (ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 23 publications
6
33
1
Order By: Relevance
“…In addition to the ionospheric feedback, highly structured diffuse auroras in the non‐patch shape were suggested to be a result of interchange instability in the magnetosphere [ Ebihara et al , 2010]. A Rayleigh‐Taylor type instability was also assumed to be the cause of finger‐like patches [ Shiokawa et al , 2010]. The spatial structures of PA1–3 may be determined by a balance between magnetic tensions and plasma pressures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the ionospheric feedback, highly structured diffuse auroras in the non‐patch shape were suggested to be a result of interchange instability in the magnetosphere [ Ebihara et al , 2010]. A Rayleigh‐Taylor type instability was also assumed to be the cause of finger‐like patches [ Shiokawa et al , 2010]. The spatial structures of PA1–3 may be determined by a balance between magnetic tensions and plasma pressures.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lui and colleagues also pointed out that there exist eastward drifting auroral patches embedded within the region of diffuse aurora [ Lui et al , 1973]. In addition, modern sensitive high resolution optical measurements from the ground showed that diffuse aurora sometimes consist of small‐scale patches of irregular shape [ Sergienko et al , 2008; Shiokawa et al , 2010]. Such auroral patches are observed in the equatorward part of the auroral oval during substorm recovery phase.…”
Section: Introductionmentioning
confidence: 99%
“…Blixt et al (2006) developed a method using optical flow analysis that extracts object motion from sequences of images by assuming that variations in brightness are solely related to object motion. For pulsating aurora, this is a significant limitation due to their prominent pulsations and constantly evolving shape (Shiokawa et al, 2010). This study details a new method of routinely and quantitatively tracking auroral forms, focusing particularly on pulsating auroral patches.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have tracked aurora by hand (e.g. Yang et al, 2015;Shiokawa et al, 2010), but there have been few attempts to apply an automatic algorithm. Blixt et al (2006) developed a method using optical flow analysis that extracts object motion from sequences of images by assuming that variations in brightness are solely related to object motion.…”
Section: Introductionmentioning
confidence: 99%